2020
DOI: 10.3390/sym12081219
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Hydrothermal Waters on Radionuclide Activity Concentrations in Natural Marble with Multivariate Statistical Analysis

Abstract: The study aims to investigate the effects of Burdur (Turkey) marble on human health by interpreting their radioactivity concentration (226Ra, 232Th, and 40K), radiological hazard parameters, chemical concentration, physical properties, and all data related to these features by using multivariate statistical methods. Chemical and radionuclide analyses were performed on marble samples. The data were interpreted by statistical analysis. According to the regression model, an increase in the concentration of vanadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Factor analysis was applied to determine the variances of the correlations that were found to be statistically signi cant in the correlation table (Yalcin et The data was found to be suitable for factor analysis, and the sampling adequacy measure was found to be greater than 0.5 (Sharma, 1996;Yalcin et al, 2020a;Yalcin et al, 2020b). The number of factors under which the data were collected was interpreted using the scree plot (Fig.…”
Section: Factor Analysismentioning
confidence: 99%
“…Factor analysis was applied to determine the variances of the correlations that were found to be statistically signi cant in the correlation table (Yalcin et The data was found to be suitable for factor analysis, and the sampling adequacy measure was found to be greater than 0.5 (Sharma, 1996;Yalcin et al, 2020a;Yalcin et al, 2020b). The number of factors under which the data were collected was interpreted using the scree plot (Fig.…”
Section: Factor Analysismentioning
confidence: 99%
“…However, in other locations, they were greater than 1 (one). The national Maximum Permissible Concentration (MPC) values for heavy metal concentrations have been determined on a national scale, [61,63]. The distribution map of the Potential Ecological Risk Index (RI) values of the study area is shown in Figure 4.…”
Section: Results Of Indexmentioning
confidence: 99%
“…The number of factors extracted for the geochemical data and the cumulative variances explained for these factors were calculated. The principal component analysis was applied to reveal the geochemical compositions of the factors statistically (Table 9) [29], [51]- [54]. The geochemical components explaining each factor were revealed.…”
Section: Factor Analysismentioning
confidence: 99%